DEVELOPMENT OF AN ANDROID-BASED APPYBUILDER LEARNING MEDIUM FOR DIGITAL SIMULATION SUBJECT AT VOCATIONAL HIGH SCHOOL: AN ADDIE MODEL APPROACH - Putri Yanti; Yandria Elmasari (JoEICT (Jurnal of Education And ICT), 2026)
The limited availability of instructional media in vocational secondary education, particularly for the Digital Simulation and Communication (SIMDIG) subject, poses a significant challenge to effective learning. This study addresses this gap by developing an Android-based mobile learning application using the AppyBuilder platform, guided by the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) instructional design model. The research was conducted at SMK Negeri 2 Tulungagung, involving expert validation by a media specialist and a subject matter expert, followed by small-group (n = 5) and large-group (n = 15) user trials with Grade X students. Data were collected through structured questionnaires and analyzed using descriptive percentage analysis. Validation results showed a media expert score of 71.4% (feasible) and a content expert score of 82.5% (highly feasible). Student trials yielded scores of 81.6% for both small-group and large-group evaluations, classified as highly feasible. These findings indicate that the developed application is appropriate and effective as a supplementary learning medium that can be accessed anytime and anywhere via Android devices. This study contributes a replicable development framework for low-code mobile learning tools in vocational education settings and highlights the potential of drag-and-drop application platforms for bridging the instructional media gap in resource-constrained schools